DETERMINANT FACTORS TO THE EXISTENCE OF AEDES AEGYPTI MOSQUITO IN THE WORKING AREA OF UBUD I HEALTH CENTER GIANYAR REGENCY, BALI - Kadek Risma Yulina Sari (The Indonesian Journal of Public Health, 2021)
Ubud I Primary Healthcare Center's working area showed an annual increase in dengue hemorrhagic fever (DHF) cases and deaths. It reported the highest DHF cases out of 13 Primary Healthcare Centers in Gianyar district. The purpose of this study was to analyze the determinants of the Aedes aegypti larvae' existence in the Ubud I Primary Healthcare Center 's working area, Gianyar district, Bali. This research was an analytic observational study with a cross-sectional study design. The research sample was 95 respondents chosen randomly using the simple random sampling technique. The high DHF cases in the Ubud I Primary Healthcare Center working area can be referred to environmental factors and community behavior factors. Interviews, larvae observation and other observations were done to collect data. Chi-square statistical test was used for data analysis. The results showed that there was a relationship between the MNE-DHF actions (p = 0.047), water PH (p = 0.001), container color (p = 0,000) to Aedes aegypti larvae' presence. On the other hand, MNE-DHF knowledge (p = 1.00) and room humidity (p = 0.357) showed no relationship with Aedes aegypti larvae' presence. Thus, it has been concluded that community actions, container color, and water pH have significant relationships with the larvae' existence. It is recommended to increase community awareness of applying more environmental management precautions.Keywords: Container’s Color, Dengue Fever, Aedes aegypti